Panorama del turismo gastronómico en Ecuador: ¿qué existe y qué falta para potenciarlo? - Dávalos Barriga, Nelson Alfredo (2017)
This research project seeks to demonstrate the current state of gastronomic tourism in the country from various perspectives of specialized chefs and journalists who talk about Haute cuisine (fine cuisine), gastronomic experts and spokespeople from public entities. The field work was carried out in the cities of Quito, Guayaquil and Cuenca and techniques such as interviews and direct observation were applied. This project gathers testimony of the issues and obstacles that the culinary industry is going through in Ecuador, but also includes the initiatives of young chefs who seek to rescue traditional cooking with new techniques of cooking. This investigation offers a gastronomic tour through 9 restaurants in the cities mentioned above.